Comprehensive Analysis of Potential Biomarkers of Acute Lymphoblastic Leukemia in Children by Using a Competing Endogenous RNA Network - Lin, Xiao-Ying; Yuen, Ka-Yuk; Chen, Hai-Lei; Shen, Miao-Na; Huang, Yan; Huang, Qian-Wen; Liu, Yong; Xu, Lu-Hong (Journal of oncology, 2022)
Acute lymphoblastic leukemia (ALL) is the most serious hematological carcinoma in adolescents. The significance of long noncoding RNAs (lncRNAs) and their regulative role in the proliferation and differentiation of myeloid cells in cancer has been recently reported. Nevertheless, key RNAs and the regulatory mechanism of competitive endogenous RNA (ceRNA) network affected by pediatric ALL are not fully illustrated. In this study, phase 2 and 3 pediatric ALL RNA profiles were extracted from the TARGET database and used to identify lncRNAs, microRNAs, and messenger RNAs in high-risk ALL and reconstruct the sponge ceRNA regulatory network. Results indicated that 44 lncRNAs, 25 miRNAs, and 115 mRNA were up/downregulated. Functional analysis with differentially expressed RNAs (DERNAs) showed enriched significant signaling pathways, including PI3K-Akt and p53 signaling cascades and other pathways associated with the tumor. Seventeen differential hub RNAs, including LINC00909, BZRAP1-AS1, C17orf76-AS1, HCG11, MIAT, SNHG5, SNHG15, and TP73-AS1, were identified. The Cox model of correlation indicated that 14 of these RNAs were associated with the progression of pediatric ALL. These findings would help clarify the regulatory role of several lncRNAs as well as provide insights into the leukemogenesis of pediatric ALL to further explore novel prognostic markers/therapeutic targets for ALL.